Trazabilidad microbiológica presente en sitios poco monitoreados y contaminados con arsénico proveniente de fuentes naturales entre los 3200 y 3400 m.s.n.m, en la parroquia de Toacaso, provincia de cotopaxi, año 2022. - Huisha Quigla, Andrea Mishel (2022)
This research aimed to determine the microbiological traceability present in poorly monitored sites and contaminated with arsenic from natural sources in the Toacaso parish at an altitude between 3200 and 3400 m.a.s.l. in January and March 2022. The project was carried out in three stages; the first is based on the biophysical study of the study area using geographic information files. Five colonies were identified, possibly of the genus Escherichia, Bacillus, and Pseudomonas. In the second stage, the arsenic (As) concentration and physicochemical parameters of the water body were determined and analyzed at the Water and Sediment Quality Laboratory (LANCAS) so that for agricultural use, they were compared with the Ministerial Agreement N°097A with Table 3 for Water Quality Criteria for Agricultural Irrigation, and human consumption with the Ecuadorian Technical Standard INEN 1108. In the third stage, Once determined the relationship between the presence of microorganisms and the existence of As through microbial isolation and Gram staining. The results obtained indicate that of the parameters analyzed, As had a significant variation in its concentration according to the first and second analysis, exceeding the MPL in March.